Early postnatal echocardiographic assessment of pulmonary blood flow in newborns with congenital diaphragmatic hernia - Kipfmueller, Florian; Heindel, Katrin; Schroeder, Lukas; Berg, Christoph; Dewald, Oliver; Reutter, Heiko M.; Bartmann, Peter; Mueller, Andreas (Journal of Perinatal Medicine, 2018)
Echocardiography is the most important tool to assess infants with congenital diaphragmatic hernia (CDH) for pulmonary hypertension (PH). The pattern of blood flow in the pulmonary artery [described as time to peak velocity (TPV)/right ventricular ejection time (RVET) ratio] provides distinct information about pulmonary arterial pressure. The aim of our study was to investigate the correlation of TPV/RVET measurements with the most commonly used classification system for PH in CDH newborns and the association of these measurements with outcome parameters. Echocardiographic measurements were obtained in 40 CDH newborns within 6 h of life. The obtained measurements were correlated with the decision for or against extracorporeal membrane oxygenation (ECMO); early mortality; total duration of mechanical ventilation and total duration of oxygen supplementation. The correlation coefficient between severity of PH and TPV/RVET measurements was -0.696 (P<0.001). Using receiver operating characteristic (ROC) analyses the optimal cutoff for TPV/RVET in order to predict the necessity for ECMO or early mortality without ECMO was 0.29 with a sensitivity of 86.7%, a specificity of 68%, a positive predictive value of 61.9% and a negative predictive value of 89.5%. Newborns with a TPV/RVET below the cutoff had a 5.9-fold risk for ECMO or early mortality, a significantly longer duration of mechanical ventilation (13.4 days vs. 7.4 days, P=0.003) and oxygen supplementation (22.4 days vs. 9.0 days, P=0.019), and a lower survival rate (76.2% vs. 100%, P=0.021). TPV/RVET is a feasible parameter to assess PH in CDH newborns with close correlation to outcome parameters.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Acceleration time; congenital diaphragmatic hernia; echocardiography; ECMO; pulmonary hypertension; time to peak velocity